Development of Geomatics Technology Curriculum for Associate Degree Programs within Project-Based Learning (PBL) - Lubis, Muhammad Zainuddin; Sari, Luthfiya Ratna; Chayati, Siti Noor; Rassarandi, Farouki Dinda; Irawan, Sudra; Anurogo, Wenang; Ghazali, Muhammad; Gustin, Oktavianto; Jamjareegulgarn, Punyawi (My University, 2025)
Geomatics technology program has strategically implemented project-based learning (PBL) in its curriculum to improve the quality of learning and prepare competent graduates in the field of geomatics. Student learning outcomes have been aligned with the Indonesian National Qualifications Framework (KKNI) Level 5, which includes capabilities in terrestrial surveying, hydrography, remote sensing, geographic information systems, and cartography. Through the PBL approach, the learning process is designed to develop students' abilities in identifying and solving real problems in the field of geomatics, as well as communicating these solutions effectively. This method encourages the development of student creativity, critical thinking, and collaboration. Alignment of Program Educational Objectives (PEOs) with the institutional mission and industry needs reflects the study program's commitment to providing superior and relevant learning experiences, as well as preparing professional and ethical graduates. The percentage of achievement of PEO and PLOs (Program Learning Outcomes) from 60% in 2019 to almost 80% in 2023, and the increase in the number of students during the period, indicate the success of the educational program in geomatics technology programs. The difference in academic achievement and behavior between the fields of hydrographic surveying (75% achievement, 17% plagiarism, 172 submissions) and oceanography (72.40% achievement, 17.40% plagiarism, 160 submissions) during 2019-2023. Through the implementation of comprehensive and integrated PBL, the geomatics technology program can effectively equip students with the technical competencies, problem-solving skills, and understanding of professional ethics needed to face challenges in the field of geomatics.
Keywords: Academic achievement; geomatics technology program; PBL; PEOs; plagiarism rates; PLOs